Antidiabetic drug metformin affects the developmental competence of cleavage-stage embryos - Nayak, Guruprasad (J Assist Reprod Genet, 2020)
PURPOSE: Metformin is the most commonly prescribed drug in the management of metabolic disorders such as polycystic ovarian syndrome (PCOS) and gestational diabetes in women of reproductive age. Insulin-sensitizing effect of metformin helps in improving from PCOS features such as hyperandrogenism, anovulation, and infertility. However, its ability to cross placental barrier raises concern about safety of the drug on early embryonic development. In this study, we evaluated the effect of metformin on the ovarian function and embryo development. METHODS: Adult Swiss albino female mice were administered with metformin (0, 50, 100, and 200 mg/kg body weight) for 4 weeks and assessed for reproductive function and preimplantation embryo development. Further, effect of metformin (0, 10, 25, 50, 100, 250, and 500 μg/mL) exposure to 2-cell-stage embryos was tested under in vitro conditions. RESULTS: Metformin did not alter the body weight, blood glucose, ovarian weight, and follicular reserve. However, the early embryo development was significantly affected in mice treated with metformin in vivo at highest dose. Moreover, embryos which were exposed to metformin in vitro showed dose-dependent decline in blastocyst rate and hatching rate. Furthermore, at highest concentration of metformin (500 μg/mL), all the embryos were arrested at compaction stage. CONCLUSION: The study revealed that metformin affects the early embryonic development and raises concern about its use during conception. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10815-020-01709-6) contains supplementary material, which is available to authorized users.